Resilient people, resilient planet a future worth choosing (United Nations, 2012)
Now more than ever, leaders need to focus on what matters most - the long-term resilience of people and the planet - the High-level Panel on Global Sustainability urged in its report presented on 30 January 2012 to UN Secretary-General Ban Ki-moon in Addis Ababa. The 22-member Panel, established by the Secretary-General in August 2010 to formulate a new blueprint for sustainable development and low-carbon prosperity, was co-chaired by Finnish President Tarja Halonen and South African President Jacob Zuma. The Panel's final report, "Resilient People, Resilient Planet: A Future Worth Choosing," contains 56 recommendations to put sustainable development into practice and to mainstream it into economic policy as quickly as possible.